Microwave Assisted-Extraction of Essential Oil from Fresh Basil (Ocium basilicium L.) Leaves - Ditta Kharisma Yolanda Putri; Atiqa Rahmawati (Program Studi Teknik Kimia Universitas Jember, 2020)
In this research, the extraction of essential oil from fresh basil leaves using solvent-free microwave extraction (SFME)and microwave hydrodistillation (MHD) method. Several parameters influence the extraction of basil oil using SFME method: microwave power, the ratio between the mass of raw material with a volume of distiller (F/D), material size, and length of extraction time. Besides, the components contained in basil oil and changes in oil gland conditions in basil leaves before and after being extracted were also evaluated. The optimum condition was obtained as follows: microwave power of 380 W, the ratio between the mass of raw material with a volume of distiller (F/D) of 0.1 g/mL, raw material size of intact (± 3 cm), with an extraction time of 60 min. Moreover, SFME has a shorter extraction time to produce yields than MHD methods. GC-MS analyzed the composition of basil oil, and there were 49 identified components. This study shows that SFME method more effective than the MHD method for extraction basil oil from fresh leaves based on time extraction and yield.